1994
DOI: 10.1182/blood.v83.12.3697.3697
|View full text |Cite
|
Sign up to set email alerts
|

RANTES- and interleukin-8-induced responses in normal human eosinophils: effects of priming with interleukin-5

Abstract: We report that responses of normal human eosinophils toward the chemokines RANTES and interleukin-8 (IL-8) are modulated and upregulated by priming with IL-5. In a modified Boyden chamber assay, we studied migratory responses toward the members of the chemokine family RANTES, monocyte chemotactic protein-1 (MCP-1), and macrophage inflammatory protein-1 alpha (MIP-1 alpha) (C-C subfamily), and IL-8, platelet factor-4 (PF-4), and neutrophil-activating peptide-2 (NAP-2) (C-x-C subfamily). These chemokines were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(40 citation statements)
references
References 41 publications
1
38
1
Order By: Relevance
“…18 Moreover, the chemokine response of normal eosinophils is modulated and upregulated by priming with IL-5. 19 Eosinophil-specific chemokines such as eotaxin recruit eosinophils from blood microvessels, and IL-5 facilitates this process by acting remotely as a hormone to stimulate the release into the circulation of a rapidly mobilizable pool of bone marrow eosinophils. 11 From these findings we speculate that both eotaxin and IL-5 are indispensable for the lesional infiltration of eosinophils.…”
Section: Discussionmentioning
confidence: 78%
“…18 Moreover, the chemokine response of normal eosinophils is modulated and upregulated by priming with IL-5. 19 Eosinophil-specific chemokines such as eotaxin recruit eosinophils from blood microvessels, and IL-5 facilitates this process by acting remotely as a hormone to stimulate the release into the circulation of a rapidly mobilizable pool of bone marrow eosinophils. 11 From these findings we speculate that both eotaxin and IL-5 are indispensable for the lesional infiltration of eosinophils.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have shown that priming of leukocytes with cytokines enhanced migration to inflammatory chemokines [4,[11][12][13][14][15][16]. In a further attempt to study the direct synergy between chemokines and inflammatory cytokines, IL-1␤ or IFN-␥ was combined with CCL2 in the THP-1 Multiscreen chemotaxis system.…”
Section: Lack Of Synergy Between Ccl2 and The Cytokines Il-1␤ And Ifnmentioning
confidence: 99%
“…Priming is a well-described phenomenon in which pre-exposure of leukocytes to TLR ligands or cytokines sensitizes cells to guarantee optimal responses to extracellular inflammatory stimuli, including chemokines [4,[11][12][13][14][15]. For example, when eosinophils were preincubated with the cytokine IL-5, their chemotactic activity toward eotaxin was enhanced [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…IL-5 plays a role in the proliferation, differentiation, and recruitment of B cells and eosinophils. In addition to roles in eosinophil proliferation, differentiation, and recruitment [18 -21], IL-5 primes eosinophils for recruitment by other cytokines and chemokines, such as IL-8 [22], RANTES [22], and eotaxin-1 [20]. Thus, IL-5 is involved in eosinophil function at multiple stages, including development, chemotaxis, and activation.…”
Section: Introductionmentioning
confidence: 99%